Dizajn električnih osobnih kolica i njihovo povezivanje s električnim vozilom u svhru povećanja autonomnosti osoba s posebnim potrebama : diplomski rad - Mišlov, Deni (D. Mišlov, 2014)
Combining the social, economic and politic approach paper introduces the topic of wheelchair industry. After the core analysis of the market state and recent developments with the solid foundations it elaborates about the possible products that can bring progress to the life of people with disabilities. Step by step it concentrates on the narrow area of ambulatory disabled people. Presenting a complete discussion on the topic of developing advanced mobility system easily brings introduction to the main task of the project. Embracing complete technical solution, from the concept idea throw mechanical and electrical design and 3D presentation at the end, offers revolutionary view in the field of wheelchair mobility. Combining existing products and developed ones presents project presents full independent system for everyday use. Technical part follows the divided form of the whole project and it separately describes each part of the system. Whole system is formed of the extern vehicle which has a function of regular wheelchair, car and lifting system. Extern vehicle is fully designed for the needs of the project and this paper contain fully description of all its parts. Car is selected from the list of product that are available on the market. Reasons of the selection are explained in detail through the paper as same as the car adjustments that project requires. Solution that covers lifting system is divided in two parts, first one offers existing project as a possible solution and other one fully self - designed one. All the designed parts are followed by 3D models which are presented in the paper. Last part of the paper includes costs and expenses offering insight in final price of the mobility system. Depending on the choice of the lifting system possibility price varies drastically. Key Words: Ambulatory disabilities, electrical wheelchair, improved mobility and independence, electrical car, 3D modeling, cascade control, PI regulator, closed loop control, Brushless Hub motor, LiFePO4.